A Review of Mercury Exposure and Health of Dental Personnel - Natasha Nagpal; Silvana S. Bettiol; Amy Isham; Ha Hoang; Leonard A. Crocombe (Elsevier, 2017)
Considerable effort has been made to address the issue of occupational health and environmental exposure to mercury. This review reports on the current literature of mercury exposure and health impacts on dental personnel. Citations were searched using four comprehensive electronic databases for articles published between 2002 and 2015. All original articles that evaluated an association between the use of dental amalgam and occupational mercury exposure in dental personnel were included. Fifteen publications from nine different countries met the selection criteria. The design and quality of the studies showed significant variation, particularly in the choice of biomarkers as an indicator of mercury exposure. In several countries, dental personnel had higher mercury levels in biological fluids and tissues than in control groups; some work practices increased mercury exposure but the exposure levels remained below recommended guidelines. Dental personnel reported more health conditions, often involving the central nervous system, than the control groups. Clinical symptoms reported by dental professionals may be associated with low-level, long-term exposure to occupational mercury, but may also be due to the effects of aging, occupational overuse, and stress. It is important that dental personnel, researchers, and educators continue to encourage and monitor good work practices by dental professionals.